Rakkety Tam / 17. - Jacques, Brian (Redwall, 2006)
Two warrior squirrels lead the battle against Gulo, a bloodthirsty wolverine who will stop at nothing to recover the Walking Stone that will give him the authority to rule the lands of ice beyond the Great Sea.